2021
DOI: 10.3389/fcvm.2021.750714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Compared With Continuous Energy Restriction on Blood Pressure Control in Overweight and Obese Patients With Hypertension

Abstract: Background and Aims: Weight-loss diets reduce body weight and improve blood pressure control in hypertensive patients. Intermittent energy restriction (IER) is an alternative to continuous energy restriction (CER) for weight reduction. We aimed to compare the effects of IER with those of CER on blood pressure control and weight loss in overweight and obese patients with hypertension during a 6-month period.Methods: Two hundred and five overweight or obese participants (BMI 28.7 kg/m2) with hypertension were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This study identified 1805 records, of which 38 RCTs involving 3039 participants were included in the NMA (Figure 1) (Antoni et al, 2018; Beaulieu et al, 2021; Bowen et al, 2018; H. Cai et al, 2019; Carter et al, 2016, 2018; Castela et al, 2022; Catenacci et al, 2016; Conley et al, 2018; Coutinho et al, 2018; Erdem et al, 2022; Fagundes et al, 2023; Gabel et al, 2019; Gray et al, 2021; Harvie et al, 2011, 2013; C. J. He et al, 2021; M. He et al, 2022; Headland et al, 2016; Hooshiar et al, 2023; Hutchison et al, 2019; Isenmann et al, 2021; Kunduraci & Ozbek, 2020; Liu et al, 2022; Maroofi & Nasrollahzadeh, 2020; McDiarmid et al, 2022; Panizza et al, 2019; Parvaresh et al, 2019; Peeke et al, 2021; Pinto et al, 2020; Pureza et al, 2020; Razavi et al, 2021; Schübel et al, 2018; Steger et al, 2021; Sundfør et al, 2018; Thomas et al, 2022; Trepanowski et al, 2017; X. Wei et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study identified 1805 records, of which 38 RCTs involving 3039 participants were included in the NMA (Figure 1) (Antoni et al, 2018; Beaulieu et al, 2021; Bowen et al, 2018; H. Cai et al, 2019; Carter et al, 2016, 2018; Castela et al, 2022; Catenacci et al, 2016; Conley et al, 2018; Coutinho et al, 2018; Erdem et al, 2022; Fagundes et al, 2023; Gabel et al, 2019; Gray et al, 2021; Harvie et al, 2011, 2013; C. J. He et al, 2021; M. He et al, 2022; Headland et al, 2016; Hooshiar et al, 2023; Hutchison et al, 2019; Isenmann et al, 2021; Kunduraci & Ozbek, 2020; Liu et al, 2022; Maroofi & Nasrollahzadeh, 2020; McDiarmid et al, 2022; Panizza et al, 2019; Parvaresh et al, 2019; Peeke et al, 2021; Pinto et al, 2020; Pureza et al, 2020; Razavi et al, 2021; Schübel et al, 2018; Steger et al, 2021; Sundfør et al, 2018; Thomas et al, 2022; Trepanowski et al, 2017; X. Wei et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The 5:2 diet had the most types of adverse effects, including increased hunger, appetite changes, dizziness, headache, mood changes, and sleep disturbances (Carter et al, 2016, 2018; Conley et al, 2018; Harvie et al, 2011, 2013; C. J. He et al, 2021; McDiarmid et al, 2022; Schübel et al, 2018; Sundfør et al, 2018). Alternate‐day fasting was primarily associated with increased hunger on fasting days (Beaulieu et al, 2021; Razavi et al, 2021), time‐restricted eating was mainly associated with dizziness and headache, and decreased appetite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Several RCTs have shown that the 5:2 diet is more effective in controlling blood glucose in patients with obesity, T2DM, and metabolic syndrome (MetS), and also significantly improves weight, BP, and adiposity factors. 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 Ramadan fasting is one of the five pillars of Islam. During Ramadan, Muslims keep fasting from sunrise to sunset, eating a large meal after sunset and a light meal before dawn.…”
Section: Dietary Patterns With Potential For Cardiometabolic Healthmentioning
confidence: 99%
“…The 5:2 diet, also listed as periodic fasting, is characterized by two fasting days (consecutive or nonconsecutive) and ad libidum intake for another 5 days 42 . Several RCTs have shown that the 5:2 diet is more effective in controlling blood glucose in patients with obesity, T2DM, and metabolic syndrome (MetS), and also significantly improves weight, BP, and adiposity factors 118–125 . Ramadan fasting is one of the five pillars of Islam.…”
Section: Dietary Patterns With Potential For Cardiometabolic Healthmentioning
confidence: 99%